Implementation Of Nursing Care In Improving Productivity And Quality Of Nursing Services Towards Nurses Performance Which Must Be Completed At A Certain Time - Bachri, Syaiful; Pannyiwi, Rahmat; Limbong, Kori; Sima, Yenny; Palembai, Asneni; Treasa, Adisty Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Recording which done contain report which required for produce assessment, diagnosis, preparing a nursing plan, implementing and then evaluating nursing activities, which have been designed in a structured, valid and accountable manner both morally and legally. The aim of the research is to determine the performance of nurses in implementing nursing care. The research method is descriptive research. This research took place in the treatment room. Hospital City Macassar with population in study this is all over Nurse who work in the Makasar City Hospital Treatment Room and the research sample is 25 Nurses using the Total Sampling Technique. Data analysis using Univariate and Bivariate analysis using statistical tests with a significance level of α = 0.05. The statistical test used is Chi-square using the SPSS computer program version 25.0 for windows. Research results using the Chi-square statistical test using SPSS regarding the relationship between workload and with performance implementation documentation care nursing in room maintenance hospital Makassar City obtained a p-value = 0.001 or less than a = 0.05, so H0 is rejected and Ha is accepted, which means that there is a relationship between workload and the implementation of nursing care documentation.